Pengaruh Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen - Ruhliandini, Putri Zafira (Ma'soem University, 2025)
This study analyzes the influence of price and service quality on purchasing decisions at Superindo in Sumedang Regency, Indonesia. The rapid growth of modern retail and shifting consumer lifestyles have intensified competition, making price and service quality critical factors in attracting customers. Using a quantitative approach, data were collected through questionnaires from 385 respondents and analyzed using SPSS 25.0 with linear regression, correlation, and hypothesis testing. Results indicate that price has a dominant positive effect, contributing 58% to purchasing decisions, while service quality contributes 27%. Simultaneously, both variables explain 60% of purchasing decision variance (R² = 0.608), with the remaining 40% influenced by unexamined factors like promotions or product availability. The findings align with previous studies but highlight the unique dynamics of mid-to-high-class retail in urban-rural areas. For Superindo, maintaining competitive pricing and improving service efficiency (e.g., staff responsiveness, checkout speed) are essential strategies. This research underscores the importance of balancing economic and experiential factors in retail, offering practical insights for market segmentation in similar regions.